2014
DOI: 10.5811/westjem.2014.9.20674
|View full text |Cite
|
Sign up to set email alerts
|

What Do Patients Want? Survey of Patient Desires for Education in an Urban University Hospital

Abstract: IntroductionThis study examines the emergency department (ED) waiting room (WR) population’s knowledge about the ED process and hospital function and explores the types of educational materials that might appeal to patients and their companions in an ED waiting room. Our goal was to identify potential high-impact opportunities for patient education.MethodsA 32-question survey about demographics, usage of primary care physicians (PCP), understanding of the ED and triage process, desire to know about delays, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 9 publications
5
26
0
Order By: Relevance
“…Prior research examining patient preferences with regard to ED care suggests patients desire increased staff communication and information regarding their ED visit ( 7 - 9 ). For example, one-third to one-half of patients do not understand the purpose of triage or why later arriving patients may be evaluated sooner ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research examining patient preferences with regard to ED care suggests patients desire increased staff communication and information regarding their ED visit ( 7 - 9 ). For example, one-third to one-half of patients do not understand the purpose of triage or why later arriving patients may be evaluated sooner ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research examining patient preferences with regard to ED care suggests patients desire increased staff communication and information regarding their ED visit ( 7 - 9 ). For example, one-third to one-half of patients do not understand the purpose of triage or why later arriving patients may be evaluated sooner ( 9 ). Patients consistently report a desire for information concerning delays, how the ED works, and information pertaining to their visit such as visitors and food ( 7 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reality reveals the implication of all these factors as problematic due to several factors like heterogeneity of patient groups and medical staff, local specialties and problems, different levels of education, languages, etc. [12].…”
Section: Introductionmentioning
confidence: 99%
“…Waiting room delays can create opportunities for clinicians to provide diseasespecific health information designed to increase their patients' health literacy by making use of information technology [15][16][17][18][19][20]. Several studies have demonstrated positive results of using multimedia technology to measure the improvement of health knowledge for both low-literacy patients and patients with higher-functional health understanding [21][22][23].…”
mentioning
confidence: 99%